Business plan : RozbitySamsung.cz - Hýbl, Tomáš; Chylíková, Hana, 1953-; Andera, Michal, 1984-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The main goal of this thesis is to create a business plan for the project called RozbitýSamsung.cz. Further, it will evaluate the whole business idea on the basis of this research. There are two main parts in this thesis. The first one describes a theoretical background needed for an elaboration of a successful business plan. The second one is focused on market research, financial plan and other necessary elements that are embodied in a business plan. The conclusion summarizes all the results from the practical part, evaluates the market situation and includes the final decision about implementation.
Vedoucí práce: Hana Chylíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses